2023
DOI: 10.3390/brainsci13111564
|View full text |Cite
|
Sign up to set email alerts
|

Navigating the Gene Co-Expression Network and Drug Repurposing Opportunities for Brain Disorders Associated with Neurocognitive Impairment

Mathew Timothy Artuz Manuel,
Lemmuel L. Tayo

Abstract: Neurocognitive impairment refers to a spectrum of disorders characterized by a decline in cognitive functions such as memory, attention, and problem-solving, which are often linked to structural or functional abnormalities in the brain. While its exact etiology remains elusive, genetic factors play a pivotal role in disease onset and progression. This study aimed to identify highly correlated gene clusters (modules) and key hub genes shared across neurocognition-impairing diseases, including Alzheimer’s diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 101 publications
0
4
0
Order By: Relevance
“…The vast heterogeneity of gliomas per grade and cell origin is one of the significant factors contributing to its difficulty responding well to treatment [27]. Through WGCNA, this study focused on identifying points at which the distinct glioma grades align genetically, since several studies have demonstrated the effectiveness of this approach in determining highly correlated genes in related diseases from a systems biology point of view [28][29][30]. Furthermore, it is able to determine pathways involved in disease networks due to its ability to investigate the interplay among the highly preserved genes.…”
Section: Signature-based Drug Repurposingmentioning
confidence: 99%
“…The vast heterogeneity of gliomas per grade and cell origin is one of the significant factors contributing to its difficulty responding well to treatment [27]. Through WGCNA, this study focused on identifying points at which the distinct glioma grades align genetically, since several studies have demonstrated the effectiveness of this approach in determining highly correlated genes in related diseases from a systems biology point of view [28][29][30]. Furthermore, it is able to determine pathways involved in disease networks due to its ability to investigate the interplay among the highly preserved genes.…”
Section: Signature-based Drug Repurposingmentioning
confidence: 99%
“…Using a deep-split parameter of 1 to obtain larger modules while maintaining efficiency in the sensitivity of the algorithm [49], we obtained 25 co-expression modules that are represented by various colors, as seen in Figure 4. The turquoise module contains 1476 genes, the blue module contains 1356 genes, the brown module contains 951 genes, the yellow module contains 761 genes, the green module contains 730 genes, the red module contains 619 genes, the black module contains 523 genes, the pink module contains 358 genes, the magenta module contains 327 genes, the purple module contains 285 genes, the green-yellow module contains 268 genes, the tan module contains 248 genes, the cyan module contains 245 genes, the salmon module contains 245 genes, the light-cyan module contains 229 genes, the midnight-blue module contains 229 genes, the grey60 module contains 209 genes, the light-green module contains 200 genes, the light-yellow module contains 183 genes, the royal-blue module contains 164 genes, the dark-red module contains 128 genes, the dark-green module contains 116 genes, the gold module contains 100 genes, the dark-turquoise module contains 78 genes, and the dark-grey module contains 44 genes.…”
Section: Identification Of Co-expressed Modulesmentioning
confidence: 99%
“…In approximating the scale-free network, the pickSoftThreshold function of the WGCNA R [17] package (v4.3.1.) was first used to plot the scale-free topology fit versus power index (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20) to estimate the appropriate soft-thresholding power (β), which is the lowest power where the scale-free topology criterion is met. This is when the distribution of the number of gene connections follows the power-law distribution, and it is usually evaluated by plotting the scale-free topology fit versus soft-thresholding power to measure the relativity of the co-expression network to the linear relationship between log of connectivity and log of connectivity probability.…”
Section: Scale-free Networkmentioning
confidence: 99%
“…Concerning this, estrogen plays a major role in regulating immune and inflammatory responses, further making it plausible to investigate the molecular underpinnings of inflammation and estrogen production in gynecological diseases. This can be made possible through weighted gene co-expression network analysis (WGCNA) [ 9 , 10 ], which is a systems biology approach that characterizes the gene associations in the gene expression data of several diseases to identify significant gene clusters (modules) and elucidate the key hub genes and main pathways that are dysregulated. The identification of upregulated and downregulated hub genes further allows for the scanning of potential already-existing drugs that can induce countering effects based on the provided gene signature while determining significant pathways opens therapeutic opportunities.…”
Section: Introductionmentioning
confidence: 99%